SENSITIVITAS MEDIA OGAWA DAN MEDIA LOWENSTEIN JENSEN TERHADAP HASIL PERTUMBUHAN KUMAN MYCOBACTERIUM TUBERCULOSIS - Pancawati Ariami; Maruni Wiwin Diarti; Yunan Jiwintarum (poltekkes kemenkes mataram, 2014)
Abstract: Referring to the national TB control program, the diagnosis made by microscopic examination of sputum by direct and definitive diagnosis by culture examination. Direct sputum examination is the gold standard method of microscopic examination of a recognized WHO TB and confirmation done by the method of culture. Research